Kmetijske strokovne podlage za celostno prostorsko načrtovanje - pristop na primeru Mestne občine Koper - Perpar, Anton (Urbani izziv, 2007)
Changed legislation of spatial planning in 2002 in Slovenia (Act on Spatial Planning - ZureP) demanded from agriculture and other sectors, guidelines or professional basis for further sectoral adjustments in the procedure of preparing of municipality spatial plan. By preparing of spatial plan of Municipality of Koper therefore expert base for agriculture has been prepared,followed with the strategy for the future development of agriculture and supplementary activities in municipality. Our approach of preparing them is presented in the article.
Keywords: agriculture; funkcije; kmetijska zemljišča; kmetijstvo; Koper; podeželje; prostorski razvoj; prostorsko planiranje; raba prostora; razvojna strategija; rural area; slv; spatial planning